HUBUNGAN RASIO KADAR KOLESTEROL TOTAL TERHADAP HDL DENGAN KEJADIAN PENYAKIT JANTUNG KORONER DI RUMAH SAKIT BADAN PENGUSAHAAN BATAM - Reza, M Faisyal; Utantyo, Nanang Rudy; Ashfiani, Sofiana (Universitas Batam, 2024)
Background: Heart disease remains the leading cause of death and disability worldwide. Coronary heart disease (CHD) has a close relationship with cholesterol and lipid levels in the body. High levels of cholesterol and lipids in the body are one of the important factors in the pathophysiological process of CHD.. Method: This research is a type of quantitative research and the method is analytic observation with a cross sectional approach conducted at the Badan Pengusahaan Batam Hospital in 2022. Data were taken from medical records.The sampling technique was random sampling with a total sample size of 68 patients. The results of the study were analyzed by frequency distribution and then tested with chi-square to determine the relationship.. Result: Based on the Chi Square test, the p value = 0.00 (p < 0.05) means that there is a significant relationship between ratio of total cholesterol to HDL levels with the incidence of coronary heart disease Conclusion: Based on the results of this study, it can be concluded that there is a significant relationship between the ratio of total cholesterol levels to HDL with the incidence of coronary heart disease in Badan Pengusahaan Batam Hospital’s At 2022.